Il compito del traduttore e le condizioni dell’afasico. Per un’interpretazione linguistica della pratica traduttiva di Hölderlin (Studia theodisca, 2019)
The paper aims to question the traditional interpretative hypotheses concerning Hölderlin’s translation practice. To this end, I will argue that the majority of Hölderlin’s “mistakes” in translating are due neither to the application of poetological or philosophical criteria, nor to occasional translator’s oversights, nor to supposed schizophrenic disease suffered by the poet. I will offer instead an interpretation of Hölderlin’s translation deficits and his peculiar translation practice (i.e. the wide use of metaphors and metonymies) by referring to Sigmund Freud’s and Roman Jakobson’s theories on aphasia and its linguistic types. In the light of these analyses, I will also focus on the inner relation between translation practice and language deficits.